N-Heterocyclic carbene catalyzed oxidative stannylation of aldehydes: a facile entry to organotin(IV) carboxylates - Reddi, Rambabu N.; Malekar, Pushpa V.; Sudalai, Arumugam (Tetrahedron Letters, 2013)
A simple protocol is described for the oxidative transformation of aldehydes to the corresponding organotin(IV) carboxylates in high yields (up to 90%) that utilizes atmospheric O-2 as the sole oxidant, N-heterocyclic carbene as catalyst (at 10 mol %), and tributyl tin chloride as stannylating agent. The uniqueness of the reaction lies in the direct conversion of aldehydes to the corresponding organotin(IV) carboxylates via stannylation of carboxylic acids, generated from the reaction of a Breslow intermediate with O-2. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carboxylic acid stannanes; N-Heterocyclic carbene; Oxidative stannylation; oxygen; Tributyltin chloride